Smart Tourism Technology (STT) with Mobile Based GPS System in Kuala Lumpur: Tag Along! - Binti Bakar, Nur Afiqah; Kumar Appadurai, Naresh (International Journal of Psychosocial Rehabilitation, 2019)
Smart Tourism Technology (STT) has becoming a trend in the tourism sector nowadays. This is because of the rapid growth of technology that affects the development of various sector in Malaysia especially the tourism industry. Journeys are becoming more likely easier with the existence of the Smart Tourism Technology for the travellers; be it a solo traveller or those who travelling in a group. However, sometimes solo travellers have difficulties when traveling alone due to various reasons such as affordability and safety. Therefore, this research paper is a discussion of the growth of Smart Tourism technology (STT), its role in the tourism sector and problem usually faced by the solo travellers. A solution for the problem mentioned is proposed which is a mobile application called TAG ALONG! as an application that helps travellers to find an accompany or friends to go and visit popular tourism places in Kuala Lumpur, Malaysia. This research will use a quantitative research method to identify the respondents’ experiences when traveling with a group and traveling solo.